KETUA NEGARA MENGIKUT KONSEP ISLAM DAN REALITI SEMASA DI MALAYSIA - Che Pa, Bharuddin (Jurnal Syariah, 2019)
This article explains the status, position and role of a Head of State from the Islamic perspective. It also describes some of the suitable honorific titles to be assumed by the Head of State in an Islamic state. This article also attempts to evaluate the extent of the role played by the Head of State of Malaysia in safeguarding the sanctity of the Islamic religion and in perpetuating the incumbent ruling system in this country.